p53 negatively regulates intestinal immunity by delaying mucosal T cell cycling - Sturm, Andreas (American Society for Clinical Investigation, 2002)
To mount an effective immune response, T cells must divide in response to antigen contact. To maintain tolerance, mucosal lamina propria T cells (LPTs) may adapt their cycling to an antigen-rich gut stimulatory environment. Here, we compared the cell cycle kinetics of LPTs and peripheral blood T cells (PBTs) before and after CD3- and CD2-mediated activation. While CD3-activated naive (CD45RA(+)) and memory (CD45RO(+)) PBTs peaked in the S and G2/M phase at 2–3 days, CD3-activated LPTs peaked at 4–6 days. In contrast, CD2 activation induced modest PBT but vigorous LPT cycling. The doubling time of CD3-activated PBTs was 1 day, while that of CD3- or CD2-activated LPTs was 2 days. LPTs failed to upregulate cyclin-dependent kinase 4 and cyclin D3, but Rb phosphorylation and cyclin A and B1 upregulation were induced by CD2 engagement. The extents of clonal expansion in LPT and PBT were comparable, indicating that LPTs’ slow replication delays but does not hinder cell division. CD2-activated LPTs displayed a striking upregulation of p53, whose blockade by antisense oligonucleotides accelerated their S phase transit time to that of CD3-activated PBTs. By slowing LPT cycling, p53 may act as a negative regulator of mucosal immunity, promoting immunological tolerance by preventing excessive T cell replication.